Pengaruh Brand Image Dan Brand Awareness Terhadap Keputusan Pembelian Sepatu Homyped Di Ramayana Mall Cikupa Tangerang - Etika Wulandari; Putri Nilam Kencana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the influence of Brand Image and Brand Awareness partially and simultaneously on the Purchase Decision of Homyped Shoes at Ramayana Mall Cikupa Tangerang. The research method used is a quantitative descriptive method. The Sampling Technique used is a probability sampling technique in the form of simple random sampling. The results of the study show that Brand Image has a positive and significant effect partially, this is evidenced by the calculated t value> t table (9.613> 1.984). This is also strengthened by the p value <Sig.0.05 or (0.000 <0.05), a correlation value of 0.697 meaning that the two variables have a strong level of relationship. The coefficient of determination is 48.5%. Brand Awareness also has a positive and significant effect partially, as evidenced by the calculated t value> t table or (11.187>1.984). This is further supported by a p-value <Sig 0.05, or (0.000 < 0.05), a correlation value of 0.749, indicating a strong relationship between the two variables. The coefficient of determination is 56.1%. Brand Image and Brand Awareness simultaneously have a significant influence on Purchasing Decisions, as evidenced by the calculated F-value > F-table, or (68.607 > 3.09). This is further reinforced by a p-value <Sig 0.05, or (0.000 < 0.05). A correlation value of 0.764 indicates a strong relationship between the independent and dependent variables. The coefficient of determination, or simultaneous contribution of influence, is 58.4%, while the remaining 41.6% is influenced by other factors.